The state in evaluation of the European Union. The example of Bosnia and Herzegovina - Bujwid-Kurek, Ewa (Balcanica Posnaniensia. Acta et studia, 2022)
The main research goal of the article is the answer to the question — what is the condition of Bosnia and Herzegovina in the assessment of the European Union. Therefore the European Parliament Resolution of 13 February 2019 on the Commission report for 2018 on Bosnia and Herzegovina, which is currently the most up-to-date document on this issue, has It should be noted that systematically, every year, a country which aspires to EU membership is subjected to such an assessment. From here, we learn what problems stand in the way of EU membership. Any country that aspires to join the EU, such as Bosnia and Herzegovina, must meet certain conditions in accordance with the Copenhagen Criteria, which were adopted by the EU in 1993 in Copenhagen. Particular attention is paid to the state of democracy, the rule of law, respect for human rights and freedoms (discrimination), corruption, ethnic relations etc. In the assessment of the analyzed European Parliament Resolution, numerous reservations are expressed regarding Bosnia and Herzegovina. In general, it can be said that the country is still struggling with many problems that prevent entry into the EU and is seen as still not fully prepared because it faces many challenges. The article was created using the research method: cade study and analysis of primary sources.